Induction and Analysis of the Alkaloid Mitragynine Content of a Mitragyna speciosa Suspension Culture System upon Elicitation and Precursor Feeding. (26th August 2013) - Mohamad Zuldin, Nor Nahazima; Said, Ikram Md.; Mohd Noor, Normah; Zainal, Zamri; Jin Kiat, Chew; Ismail, Ismanizan
Abstract : This study aimed to determine the effects of different concentrations and combinations of the phytohormones 2, 4-dichlorophenoxy acetic acid (2, 4-D), kinetin, 6-benzylaminopurine (BAP), and 1-naphthaleneacetic acid (NAA) on callus induction and to demonstrate the role of elicitors and exogenous precursors on the production of mitragynine in a Mitragyna speciosa suspension culture. The best callus induction was achieved from petiole explants cultured on WPM that was supplemented with 4 mg L −1 2, 4-D (70.83%). Calli were transferred to liquid media and agitated on rotary shakers to establish Mitragyna speciosa cell suspension cultures. The optimum settled cell volume was achieved in the presence of WPM that contained 3 mg L −1 2, 4-D and 3% sucrose (9.47 ± 0.4667  mL). The treatment of cultures with different concentrations of yeast extract and salicylic acid for different inoculation periods revealed that the highest mitragynine content as determined by HPLC was achieved from the culture treated with 250 mg L −1 yeast extract (9.275 ± 0.082  mg L −1 ) that was harvested on day 6 of culturing; salicylic acid showed low mitragynine content in all concentrations used. Tryptophan and loganin were used as exogenous precursors; the highest level of mitragynine production was achieved in cultures treated with 3  μ M tryptophan and harvested at 6 days (13.226 ± 1.98  mg L −1 ).